A systematic review of the safety and efficacy of distal coronary artery anastomotic devices in MIDCAB and TECAB surgery. (October 2016) - Soylu, Erdinc; Harling, Leanne; Ashrafian, Hutan; Attaran, Saina; Athanasiou, Christina; Punjabi, Prakash P; Casula, Roberto; Athanasiou, Thanos
Background: Minimally invasive direct coronary artery bypass (MIDCAB) and totally endoscopic coronary artery bypass (TECAB) techniques may improve recovery and reduce hospital stay following coronary artery bypass surgery (CABG). However, working in a limited space with indirect visualisation would greatly benefit from a simple, high-quality and reproducible automated distal anastomotic method. Several devices have been developed; however, their uptake has been limited due to uncertainty around their impact on patient outcomes. Methods: A systematic review of the literature identified six studies, incorporating 139 subjects undergoing MIDCAB or TECAB surgery using a distal anastomotic device. Results: The overall 30-day mortality was 0.7% (1/137). No cardiac specific mortality was observed. For each outcome of perioperative myocardial infarction (MI), postoperative stroke and haemorrhage, only a single event was observed for each (n=1/136, 1/138 and 1/136, respectively). The overall device failure rates were low, with the use of additional sutures only reported in a single case with the Magnetic Vascular Port (MVP) device. Anastomotic time ranged from a mean of 3.32 minutes with the MVP device to 20 minutes with the C-Port device. Conclusions: These results demonstrate the overall acceptable early outcomes of distal anastomotic devices for use in minimally invasive coronary bypass surgery. Future research should focus on designing adequately powered, comparative, randomised trials, focusing on major adverse cardiac and cerebrovascular events (MACCE) outcomes in both the short and long-term, with clear case-by-case reasons for device failure and a comparison of anastomotic times. In this way, we may determine whether such devices will facilitate the minimal access and robotic coronary procedures of the future.